2011
DOI: 10.1002/app.33766
|View full text |Cite
|
Sign up to set email alerts
|

Morphologies and properties of nanocomposite films based on a biodegradable poly(ester)urethane elastomer

Abstract: Biodegradable poly(ester)urethane (PU) elastomer-based nanocomposite films incorporated with organically modified nanoclay were prepared with melt-extrusion compounding followed by a casting film process. These films were intended for application as biodegradable food packaging films, with their enhanced gas barrier, mechanical, and thermal properties and good flexibility. From both X-ray diffraction measurements and transmission electron microscopy observations, the coexistence of intercalated tactoids and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This result can be ascribed to the decomposition of low molecular weight organic modifiers (methyl tallow bis‐2‐hydroxyethyl quaternary ammonium) adsorbed on the clay surface. For the nanocomposites containing nanoclays treated with organic modifiers, the initial degradation temperatures have been usually observed to be reduced with increase of added nanoclay content because of decomposition phenomena of organic modifiers at initial low temperature range . As the true thermal stability parameters, therefore, the degradation temperatures at 50% weight loss ( T 50 ) were obtained from the thermograms in the higher temperature region after elimination of surfactants, which were determined as 386, 387, 389, and 392°C for the neat EVOH, EVCL3, EVCL5, and EVCL7, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This result can be ascribed to the decomposition of low molecular weight organic modifiers (methyl tallow bis‐2‐hydroxyethyl quaternary ammonium) adsorbed on the clay surface. For the nanocomposites containing nanoclays treated with organic modifiers, the initial degradation temperatures have been usually observed to be reduced with increase of added nanoclay content because of decomposition phenomena of organic modifiers at initial low temperature range . As the true thermal stability parameters, therefore, the degradation temperatures at 50% weight loss ( T 50 ) were obtained from the thermograms in the higher temperature region after elimination of surfactants, which were determined as 386, 387, 389, and 392°C for the neat EVOH, EVCL3, EVCL5, and EVCL7, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, both tensile properties of modulus and elongation for the materials are not able to be improved simultaneously by only one technical method. It has been observed that the inclusion of inorganic clay possessing very high stiffness as well as high aspect ratio into polymer matrix improved the strength and modulus, but resulted in a reduction in the tensile elongation responsible for the flexibility of the nanocomposite film …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Major challenges associated with the incorporation of nanoparticles into the polymer matrix include incompatibility between nanoparticles and the polymer, the agglomerating tendency of fillers and the poor dispersion of nanoparticles in polymers. Several strategies have been developed to enhance the uniform dispersion of nanoparticles in the polymer matrix . Most of these methods require an additional step of ultrasonication for the dispersion of nanoparticles in an organic solvent followed by mixing with the polymer.…”
Section: Introductionmentioning
confidence: 99%